2007
DOI: 10.1016/j.compscitech.2007.03.033
|View full text |Cite
|
Sign up to set email alerts
|

New peel stopper concept for sandwich structures

Abstract: The paper addresses the damage tolerance of sandwich structures, where the prevention and limitation of delamination failure are highly important design issues. Due to the layered composition of sandwich structures, face-core interface delamination is a commonly observed failure mode, often referred to as peeling failure. Peeling between the sandwich face sheets and the core material drastically diminishes the structural integrity of the structure. This paper presents a new peel stopper concept for sandwich st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 17 publications
3
52
0
1
Order By: Relevance
“…The basic principle of the so-called 'peel stopper' is to deflect the crack away from the face sheet/core interface into the core, so that the crack path follows the boundary of the peel stopper. The functionality of the crack stopper was validated experimentally using three-point bend tests in which sandwich beams with aluminium or GFRP face sheets and Divinycell H60 PVC foam core were studied [5,6]. It was shown that interfacial cracks that were initiated by core shear failure were successfully deflected and arrested by the peel stopper.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The basic principle of the so-called 'peel stopper' is to deflect the crack away from the face sheet/core interface into the core, so that the crack path follows the boundary of the peel stopper. The functionality of the crack stopper was validated experimentally using three-point bend tests in which sandwich beams with aluminium or GFRP face sheets and Divinycell H60 PVC foam core were studied [5,6]. It was shown that interfacial cracks that were initiated by core shear failure were successfully deflected and arrested by the peel stopper.…”
Section: Introductionmentioning
confidence: 99%
“…A different concept was proposed by Jacobsen et al [5][6][7][8], where the crack stopper was manufactured from a PolyUrethane (PU) material with stiffness properties similar to those of the foam core materials. A key element in the design was to confine and arrest the growth of the interfacial crack.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations